Prevalence of Candida species in urinary tract infections among hospitalized patients in medical wards at Teaching Hospital, Jaffna - Mahinsha, J; Elaxchiya, A; Akalya, T; Gnankaruniyan, TJ (Faculty of Allied Health Sciences, University of Jaffna, Sri Lanka., 2025)
Urinary tract infections (UTIs) are common, but Candida species are increasingly identified among hospitalized patients with risk factors such as prolonged stay, antibiotic use, catheterization, and immunosuppression. Antifungal resistance in Candida species has complicated patient management. A limited number of studies have been conducted in Sri Lanka related to this study. Objectives: This study determines the prevalence of Candida species causing UTIs among patients admitted to the Medical wards of the Teaching Hospital, Jaffna. Methodology: A descriptive, cross-sectional study was conducted among 271 patients suspected of UTIs. Based on a convenient sampling technique, participants were selected. Mid-stream urine and catheterized urine samples were processed in the Microbiology Laboratory. Data were analyzed by using SPSS version 20 by chi-square tests (p < 0.05). Results: The results revealed a prevalence of 12.2%. Out of 271 participants, 33 (12.2%) were positive for Candida species. Candida albicans (48.5%) is the most predominant species, which is consistent with other studies. Followed by Candida glabrata (24.2%), Candida krusei (21.2%), and Candida tropicalis (6.1%). Females had a significantly higher prevalence compared to males (p=0.005), and prevalence was higher among patients above 60 years (p=0.082). Conclusions: While Candida albicans is still predominant, the increasing presence of non-albicans species highlights the importance of routine species–level identification.
Keywords: Candiduria; Prevalence; Urinary tract infection; Candida species